2017
DOI: 10.18632/oncotarget.15931
|View full text |Cite
|
Sign up to set email alerts
|

TMPRSS2:ERGgene fusion variants induce TGF-β signaling and epithelial to mesenchymal transition in human prostate cancer cells

Abstract: TMPRSS2:ERG (T/E) gene fusions are present in approximately 50% of all prostate cancer (PCa) cases. The expression of fusion mRNAs from distinct T/E variants is associated with clinicopathological parameters, while the underlying molecular processes remain unclear. We characterized the molecular mechanisms and functional implications caused by doxycycline (Dox)-inducible overexpression of the frequent T/E III and VI fusion variants in LNCaP cells. Induction of T/E expression resulted in increased cellular migr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 61 publications
(87 reference statements)
1
29
0
Order By: Relevance
“…TGF- /Smad signaling pathway plays the important roles in the regulation of proliferation, migration and epithelial-mesenchymal transition (EMT) of prostate cancer [ 9 , 10 , 11 ]. Therefore, we investigated whether lncRNA ANRIL could regulate the TGF- /Smad signaling pathway in prostate cancer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TGF- /Smad signaling pathway plays the important roles in the regulation of proliferation, migration and epithelial-mesenchymal transition (EMT) of prostate cancer [ 9 , 10 , 11 ]. Therefore, we investigated whether lncRNA ANRIL could regulate the TGF- /Smad signaling pathway in prostate cancer.…”
Section: Resultsmentioning
confidence: 99%
“…In prostate cancer, TFG- could promote PI3K/AKT signaling and cell migration through the TRAF6-mediated ubiquatylation of p85 [ 11 ]. TMPRSS2:ERG gene fusion activated the TFG- signaling via increasing VIM, MMP1, CDH2 and SNAI2, and induced the epithelial to mesenchymal transition in human prostate cancer cells [ 10 ]. The smad7 was commonly regulated by ubiquitin-mediated degradation via Smurf2 and ITCH, however, how its phosphorylation was regulated was still needed to explore.…”
Section: Discussionmentioning
confidence: 99%
“…EMT is a crucial phenotypic conversion during cancer progression ( 27 , 28 ) and is a process by which cancer cells lose their polarized epithelial structures and acquire plastic and high motile mesenchymal properties ( 29 , 30 ). Clinicopathological studies revealed that EMT strongly correlated with poor histological differentiation, destruction of tissue integrity and metastasis ( 31 , 32 ). Therefore, EMT is considered to be an exclusive phenotypic switch for the invasion and metastasis of cancers including GC ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the recurrent nature of this genomic alteration, ETS gene fusions alone are not sufficient to initiate tumorigenesis; other events such as PTEN loss or phosphatidylinositol 3-kinase ( PI3K ) /AKT activation must concomitantly be present for cellular transformation to occur [ 25 , 26 ]. ERG is a master transcription factor that interacts with several other cofactors to regulate the expression of target genes and modulate multiple biological processes that favor oncogenic transformation [ 27 , 28 , 29 , 30 ]. ERG induces the expression of the metalloproteinase MMP3 and the plasminogen activator genes PLAT and PLAU , facilitating invasion of the T2E-positive PCa cell line VCaP [ 30 ].…”
Section: The Genomic Landscape Of Primary Prostate Cancermentioning
confidence: 99%
“…ERG induces the expression of the metalloproteinase MMP3 and the plasminogen activator genes PLAT and PLAU , facilitating invasion of the T2E-positive PCa cell line VCaP [ 30 ]. In LNCaP T2E cell models, overexpression of the fusion resulted in the activation of the TGF-β signaling pathway and induction of epithelial to mesenchymal transition [ 29 ]. Moreover, by binding to the AR promoter region, ERG hinders AR-mediated, cell-specific differentiation of prostate cells [ 28 ].…”
Section: The Genomic Landscape Of Primary Prostate Cancermentioning
confidence: 99%